The Teleparallel Lagrangian and Hamilton-Jacobi formalism - Pimentel, B. M.; Pompeia, P. J.; da Rocha-Neto, J. F.; Teixeira, R. G. (Kluwer Academic/plenum Publ, 2003)
We analyze the Teleparallel Equivalent of General Relativity (TEGR) from the point of view of Hamilton-Jacobi approach for singular systems.
Keywords: gravity; Hamiltonian; torsion